Aktivitas Antioksidan dan Karakteristik Body Lotion dengan Perbedaan Konsentrasi Ekstrak Daun Jeruju ( Acanthus ilicifolius ). - Almaida Mulya; Rifki Prayoga Aditia; Afifah Nurazizatul Hasanah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
This study aimed to determine the effect of different concentrations of Acanthus ilicifolius leaf extract on antioxidant activity and physical characteristics of body lotion. The formulations were prepared with extract concentrations of 0, 2, 4, and 6 g. Antioxidant activity was tested using the DPPH method, while physical evaluations included pH, homogeneity, emulsion type, organoleptic properties, and skin moisture. The results showed that increasing extract concentration increased antioxidant activity, with the highest inhibition value found in P3 (76.19%). All formulations were homogeneous and had oil-in-water emulsion type. The pH values ranged from 6.92 to 7.93 and were within acceptable limits. Organoleptic test showed decreased panelist preference at higher extract concentrations. Moisture test showed no signific ant difference, but all formulations increased skin hydration.